The Application of Inclusive Education Services in Shaping The Character of Students - Suharyanto H Soro; Nana Herdiana Abdul Rahman; Khoirunnisa Khoirunnisa; Wiwi Widyaningsih (Global Education Journal, 2026)
Inclusive education is one of the educational approaches that guarantees the learning rights of all students, including children with special needs (ABK). However, in practice, the implementation of inclusive education services in primary schools still faces various challenges, especially limited human resources, and understanding of school residents. This study aims to describe the application of inclusive education services in shaping the character of regular students in interacting with students with special needs. The research uses a qualitative research paradigm with a case study approach. The data collection method was carried out through non-participatory observation, structured interviews, and documentation studies. Data analysis is carried out in the stages of data reduction, data presentation, and conclusion drawn, and supported by triangulation of sources and techniques to ensure the validity of the data. The results of the study show that (1) inclusive education services are implemented through the combination of students with special needs and regular students in one class, accompanied by material modification, learning differentiation, use of visual media, and group learning with peer assistance; (2) The implementation of these services has a positive impact on the development of students' character, especially empathy, tolerance, cooperation, social concern, and mutual respect; (3) The implementation of inclusion still faces obstacles in the form of limited special assistant teachers, minimal support facilities, and gaps in abilities between students. This study concludes that the implementation of inclusive education services can form a positive character of students.